2002
DOI: 10.1183/09031936.02.00822002
|View full text |Cite
|
Sign up to set email alerts
|

Apparent but not real increase in asthma prevalence during the 1990s

Abstract: The authors investigated changes in asthma prevalence and perception of bronchoconstriction over 6 yrs in adults of Newcastle-upon-Tyne.Postal questionnaires were sent to 6,000 subjects aged 20-44 yrs in 1992-1993 and 1998-1999. Random samples of 600 responders had assessments of atopy, airway responsiveness, and their ability to perceive methacholine-induced bronchoconstriction. The prevalences of asthmatic symptoms, physician-diagnosis, and medication use increased by an average of 4.4%, particularly in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 29 publications
1
48
0
1
Order By: Relevance
“…Using varying definitions, studies have shown that, as we observed, the prevalence of DDA has increased more than have symptoms [31,32]. Other studies have not found significant changes in asthma prevalence in adults [33,34], although the latter study [34] was confined to adults aged .70 yrs.…”
Section: Resultsmentioning
confidence: 45%
“…Using varying definitions, studies have shown that, as we observed, the prevalence of DDA has increased more than have symptoms [31,32]. Other studies have not found significant changes in asthma prevalence in adults [33,34], although the latter study [34] was confined to adults aged .70 yrs.…”
Section: Resultsmentioning
confidence: 45%
“…Estimates of the proportion of 'ghosts' among non-responders have varied considerably and were up to 25% in studies in North East England. 9,14,15 Were there to have been an actual rise in the prevalence of ghost patients, our results would in fact underestimate the decline in survey response rates. Sender recognition may be a further factor affecting response.…”
Section: T I O N P R O H I B I T E Dmentioning
confidence: 60%
“…29 In our study, more than 75% of the participants in whom asthma was eventually excluded reported dyspnea and wheezing in the 12 months before study entry. This increase in reporting of symptoms is probably occurring in concert with physicians' increased willingness to make a diagnosis of asthma in response to respiratory symptoms.…”
Section: Discussionmentioning
confidence: 96%